The Oil is Dying? Long Live its "Heritage"! - Stephan Hauser (A+BE: Architecture and the Built Environment)
Oil is a dangerous product. Its transport, storage and refining present numerous environmental and health challenges. Local, national and European regulators have taken steps to locate it in space since the beginning of industrial oil drilling in the 1860s. But key leaders of the oil industry in Northwest Europe, and beyond, have also served as policy makers and aimed to keep legal constraints (decrees, laws, taxes) as limited as possible to prevent the emergence of obstacles in the development of their industry. This process led to a cruel lack of anticipation in the design of rules and urban spaces when dealing with safety. Public authorities continuously established limited frames upon the oil industry and wrote rules in general terms to protect this strategic industry. Today, the pollution and the risks oil companies generated restrict opportunities for the future re-use of industrial sites, and there has been little done on the law-making scale to guide the transformation of oil spaces. Using the case of port cities like Dunkirk, in France, that have emerged as oil ports for their respective countries over the last 150 years, this thesis examines the emergence and application of spatial and environmental regulations along with oil industrial expansion. The objective is to highlight the need to shift from the current reactive process of improving legal frames after a disaster to one that anticipate and deal with the visible and invisible oil heritage.